Factors influencing the efficiency of cellphone-based CBT for treating sleep disorders - Hu, Nannan; Xu, You; Mao, Hongjing (Frontiers in Psychiatry, 2022)
Objective This survey aimed to better comprehend the factors influencing patient response to insomnia treatment. Methods We conducted an online survey. A total of 1,395 patients completed the questionnaire at baseline. Insomnia, anxiety and depressive symptoms were evaluated using the Pittsburgh Sleep Quality Index (PSQI), 7-item Generalized Anxiety Disorder assessment (GAD-7) and 9-item Patient Health Questionnaire (PHQ-9), respectively. A total of 488 patients completed at least two surveys (baseline and monthly surveys thereafter) and reported that the online CBT was effective at the 1-year follow-up. The 488 patients were divided into three groups: the rapid (treatment effective at 4 weeks), intermediate (4–16 weeks), and delayed-response group (over 16 weeks). Results Analysis of the demographic characteristics of the 488 patients did not reveal significant sex differences among the three groups (P = 0.111). However, the groups significantly differed in age (P = 0.001) and education (P = 0.006). Compared to the rapid response group, the delayed-response group had a higher mean age (P < 0.01) and a slightly lower level of education. The duration of the disorder was longer in the delayed-response group. Multivariate logistic regression showed that male sex, junior high school education, and higher PSQI were independent risk factors for the delayed response to treatment. Conclusion Many factors affected the efficiency of insomnia treatment. Male sex, junior school education, and a high PSQI score predicted delayed response to insomnia treatment.